Restructuring secretarial education to meet advanced technology for Nigeria economic development - Ehidiamhen, Sylvester (Journal of Professional Secretaries and Office Administrators, 2014)
Secretarial Education system had suffered a lot of setbacks in terms of teaching and learning in technologies. Owing to the advancement in office technology, the curriculum of secretarial education seemed not to be detail in the tertiary institution. Contemporary use of office technologies were created gap between the secretarial graduate and other professional bodies in terms of challenge in the use of technologies after graduation. Therefore, a detailed curriculum in secretarial education would help to close the wide gap created in availability and use of ICTs across the world. This paper is focused on the restructuring of secretarial education curriculum, and look at lack of qualified lecturers and the provision of ICTs materials. Suggestions and necessary recommendations will be offered for developing countries like Nigeria to leap-frog the educational stage and transform their economies into high value-added information and economies that can compete with the advanced countries in the globe.